Aid and exchange rates in sub-Saharan Africa: Nomore dutch disease? - Oliver Morrissey; Lionel Roger; Lars Spreng (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2019)
Given the significant inflows of foreign aid to sub-Saharan Africa (SSA) the possibility of Dutch Disease has been a concern. Most macroeconomic models predict that aid inflows, especially if large and/or unanticipated (shocks), will lead to an appreciation of the real exchange rate and undermine the competitiveness of the economy. Empirical evidence is inconclusive, but a common presumption is that aid has been associated with Dutch Disease effects in SSA. Previous empirical studies rely on annual data and few include data since themid-2000s. This paper focuses on themore recent period employing monthly time series data for ten countries over 2001 to 2017 to estimate a structural VAR. For the majority of countries aid has no or a minimal effect on the real exchange rate; there is evidence of a significant real appreciation in only two countries. Additional analysis shows that commodity export prices are a more important determinant of the real exchange rate, with an effect on average twice that of aid. The paper conjectures that the absence of a Dutch Disease effect since the 2000s is due to a declining level of aid inflows and improved macroeconomic management.
Keywords: F31; F35; O11; O55; 330; Foreign Aid; Exchange Rates; Dutch Disease; sub-Saharan Africa